Brucella abortus Infection of Placental Trophoblasts Triggers Endoplasmic Reticulum Stress-Mediated Cell Death and Fetal Loss via Type IV Secretion System-Dependent Activation of CHOP - Byndloss, Mariana X. (mBio, 2019)
Subversion of endoplasmic reticulum (ER) function is a feature shared by multiple intracellular bacteria and viruses, and in many cases this disruption of cellular function activates pathways of the unfolded protein response (UPR). In the case of infection with Brucella abortus, the etiologic agent of brucellosis, the unfolded protein response in the infected placenta contributes to placentitis and abortion, leading to pathogen transmission. Here we show that B. abortus infection of pregnant mice led to death of infected placental trophoblasts in a manner that depended on the VirB type IV secretion system (T4SS) and its effector VceC. The trophoblast death program required the ER stress-induced transcription factor CHOP. While NOD1/NOD2 expression in macrophages contributed to ER stress-induced inflammation, these receptors did not play a role in trophoblast death. Both placentitis and abortion were independent of apoptosis-associated Speck-like protein containing a caspase activation and recruitment domain (ASC). These studies show that B. abortus uses its T4SS to induce cell-type-specific responses to ER stress in trophoblasts that trigger placental inflammation and abortion. Our results suggest further that in B. abortus the T4SS and its effectors are under selection as bacterial transmission factors.